2017
DOI: 10.1002/jcb.25969
|View full text |Cite
|
Sign up to set email alerts
|

The Opportunity of Precision Medicine for Breast Cancer With Context‐Sensitive Tumor Suppressor Maspin

Abstract: To improve the precision of molecular diagnosis and to develop and guide targeted therapies of breast cancer, it is essential to determine mechanisms that underlie the specific tumor phenotypes. To this end, the application of a snapshot of gene expression profile for breast cancer diagnosis and prognosis is fundamentally challenged since the tissue-based data are derived from heterogonous cell types and are not likely to reflect the dynamics of context-dependent tumor progression and drug sensitivity. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…RT-qPCR assays revealed that the expression of maspin affected the gene expressions of cyclin D1, p21, vimentin MMP2, and MMP9 in xenograft tumors, which suggested that maspin may modulate these genes to regulate tumor growth in vivo. A previous study indicated that maspin blocked MMP9 expression in prostate carcinoma cells [25]. The previously mentioned genes are also potential target genes of HDAC1 indicating that maspin may correlate with the HDAC1 activity.…”
Section: Discussionmentioning
confidence: 86%
“…RT-qPCR assays revealed that the expression of maspin affected the gene expressions of cyclin D1, p21, vimentin MMP2, and MMP9 in xenograft tumors, which suggested that maspin may modulate these genes to regulate tumor growth in vivo. A previous study indicated that maspin blocked MMP9 expression in prostate carcinoma cells [25]. The previously mentioned genes are also potential target genes of HDAC1 indicating that maspin may correlate with the HDAC1 activity.…”
Section: Discussionmentioning
confidence: 86%
“…A particular member of the serpin family, maspin, has been previously studied because of its inhibitory potential in breast and prostate cancer development [100]. Recently, the designing novel maspin-based chemotherapeutic agents with improved anti-cancer potency was suggested [101]. Katsukawa and co-workers [102] suggested that serpin 5 secreted by epithelial cells acts as a component of the extracellular surveillance system that facilitates the clearance of premalignant epithelial cells.…”
Section: Serine Protease Inhibitors: Anti-proliferative and Anti-mmentioning
confidence: 99%
“…SERPINB5 is an epithelial-cell-specific member of the SERPIN family that lacks serine protease inhibition activity. Not much is known about its cellular functions in cancer, yet it has been implicated as cancer susceptibility gene and a prognostic factor in several cancer types (33). It has been also attributed a role as an exosomal protein (34).…”
Section: Resultsmentioning
confidence: 99%